2022
DOI: 10.1038/s41467-022-32176-5
|View full text |Cite
|
Sign up to set email alerts
|

RNA-binding protein RBM3 intrinsically suppresses lung innate lymphoid cell activation and inflammation partially through CysLT1R

Abstract: Innate lymphoid cells (ILC) promote lung inflammation in asthma through cytokine production. RNA-binding proteins (RBPs) are critical post-transcriptional regulators, although less is known about RBPs in ILC biology. Here, we demonstrate that RNA-binding motif 3 (RBM3) is highly expressed in lung ILCs and is further induced by alarmins TSLP and IL-33. Rbm3−/− and Rbm3−/−Rag2−/− mice exposed to asthma-associated Alternaria allergen develop enhanced eosinophilic lung inflammation and ILC activation. IL-33 stimul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Although it is currently unclear when and where trNK cell commitment occurs and whether the cellular states in spleen and skin are actually connected at this day 8 pi “snapshot” of gene expression, this analysis highlighted several interesting genes regulated along this trajectory, including the following: Satb1 , a chromatin organizer with a function in maintaining the naive state of CD8 + T cells before activation, 38 the lysine demethylase 6b ( Kdm6b ) involved in effector differentiation of CD8 + T cells and NK cells, 39 and the RNA-binding protein 3 ( Rbm3 ) that has been suggested to increase β-catenin signaling, and thereby activity of Tcf/Lef transcription factors, and to restrain activation of ILC2s. 40 Other interesting genes include Stat3 , which regulates responsiveness to cytokines, Ifngr1 , involved in ILC1 differentiation, 41 and Smad7 , which can antagonize TGF-β signaling and thereby may inhibit signals from concomitantly upregulated Tgfb1 . 42 …”
Section: Resultsmentioning
confidence: 99%
“…Although it is currently unclear when and where trNK cell commitment occurs and whether the cellular states in spleen and skin are actually connected at this day 8 pi “snapshot” of gene expression, this analysis highlighted several interesting genes regulated along this trajectory, including the following: Satb1 , a chromatin organizer with a function in maintaining the naive state of CD8 + T cells before activation, 38 the lysine demethylase 6b ( Kdm6b ) involved in effector differentiation of CD8 + T cells and NK cells, 39 and the RNA-binding protein 3 ( Rbm3 ) that has been suggested to increase β-catenin signaling, and thereby activity of Tcf/Lef transcription factors, and to restrain activation of ILC2s. 40 Other interesting genes include Stat3 , which regulates responsiveness to cytokines, Ifngr1 , involved in ILC1 differentiation, 41 and Smad7 , which can antagonize TGF-β signaling and thereby may inhibit signals from concomitantly upregulated Tgfb1 . 42 …”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, our data do suggest a previously unknown mechanism for APA regulation in T cell via induced expression of RBM3 early upon T cell activation. RBM3 is a stress-induced protein that has been implicated in cytokine expression in innate lymphoid cells 39 , and has neural protective activity 40 . We show here that expression of RBM3 mRNA and protein are markedly enhanced early after T cell activation and this correlates with 3′UTR shortening of genes that have an RBM3 binding motif immediately overlapping the distal PAS site.…”
Section: Discussionmentioning
confidence: 99%
“…First, even though multiple cytokines (e.g., IL-12, IL-18) have been shown to have important regulatory roles on ILC1s function, mRNA stability-related RBPs in ILC1s have not been identified, which merits further investigation. Second, several RBPs have been shown to have important roles in the regulation of ILC2s function, including regnase-1, TTP, and RNA-binding protein 3 (RBM3) ( 124 ). Specifically, regnase-1 and TTP have broad roles in mRNA stability in ILCs and other cell subsets.…”
Section: Discussionmentioning
confidence: 99%
“…However, RBM3 has a potentially specific role in ILC2s because studies have shown that RBM3 deficiency has no effects on the numbers of NK cells, T cells, or B cells in mice. Hence, RBM3 might be an ILC2s-specific RBP in immune cells ( 124 ). Third, a few studies have reported that circRNAs can regulate downstream mRNAs stability in ILC3s indirectly ( 125 127 ).…”
Section: Discussionmentioning
confidence: 99%